1999
DOI: 10.1038/sj.onc.1202551
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a new isoform of the tumor susceptibility TSG101 protein lacking a leucine zipper domain in Burkitt lymphoma cell lines

Abstract: The tumor susceptibility gene, TSG101, has been identi®ed as a candidate tumor suppressor gene. We have examined the expression of TSG101 in Burkitt lymphoma cell lines. Several aberrant messages were detected in all cell lines. Aberrant splice donor sites are located within exon 1 at positions 132, 154, 172 and 284. Splice acceptors are located at positions 847 and 1054 within exon 5. The aberrant messages are coexpressed with a normal message and could be the result of additional splicing reactions of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…However, excessive production of TSG101 also can promote abnormal cell growth (10), consistent with evidence for a cellular imperative to maintain TSG101 levels within a narrow range (19). Aberrant splicing of, partial deletions in, or overproduction of TSG101 protein have been reported to occur in human cancers (45)(46)(47)(48). Consistent with a crucial role of the intracellular level of TSG101 in determining its actions is evidence that cells that totally lack TSG101 cannot be propagated (8,9), whereas a lesser deficiency of TSG101 allows cell survival while still yielding prominent effects on endosomal trafficking and other biological processes (10,17,23,24).…”
Section: Discussionmentioning
confidence: 70%
“…However, excessive production of TSG101 also can promote abnormal cell growth (10), consistent with evidence for a cellular imperative to maintain TSG101 levels within a narrow range (19). Aberrant splicing of, partial deletions in, or overproduction of TSG101 protein have been reported to occur in human cancers (45)(46)(47)(48). Consistent with a crucial role of the intracellular level of TSG101 in determining its actions is evidence that cells that totally lack TSG101 cannot be propagated (8,9), whereas a lesser deficiency of TSG101 allows cell survival while still yielding prominent effects on endosomal trafficking and other biological processes (10,17,23,24).…”
Section: Discussionmentioning
confidence: 70%
“…The synthesis of cDNA has been previously reported (Ferrer et al, 1999). From this cDNA 1 ml was used as substrate to amplify by PCR dierent fragments of the cDNA in order to make dierent constructions of fusion proteins with dierent types of expression vectors.…”
Section: Isolation Of Rna and Cdna Synthesismentioning
confidence: 99%
“…The different types of messages were determined following the same methodological strategy previously described in Burkitt lymphomas. 6 The message coding for isoform B, when present, is readily detected (Figure 1). Nucleotide sequencing of this new B message confirmed that it joins nucleotide 283, in exon 3, to nucleotide 1055, within exon 9, using a cryptic splice acceptor site, and thus with a different carboxy terminus.…”
Section: To the Editormentioning
confidence: 99%
“…We have recently detected, in 77% of Burkitt's lymphoma cell lines, the presence of a new alternatively spliced message that codes for a 17-kDa protein (isoform B) that lacks the coiled-coil (leucine zipper) domain, but that partially retains the amino terminus with the ubiquitination inhibitor domain. 6 This message has not been detected in normal cells despite the fact that a subpopulation of normal cells is capable of forming alternatively spliced non-coding messages. This isoform B, coded by the new transcript, might have a different function due to the loss of specific proteinprotein interactions mediated by the coiled-coil domain (leucine zipper) in the carboxy terminus, and consequent loss of its transcriptional regulation role.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation